A hierarchy of models of axisymmetric wave propagation in a fluid-filled periodic cylindrical shell composed of high-contrast cells. (February 2020) - Sorokin, S.V.; Gautier, F.; Pelat, A.
Highlights: A hierarchy of models of axisymmetric wave propagation in fluid-loaded pipes. Pass- and stop-bands of a periodic pipe composed of high-contrast cells. Eigenfrequency analysis of a unit periodicity cell. Abstract: This paper is concerned with modeling of axisymmetric wave propagation in an elastic periodic cylindrical shell under internal heavy fluid loading. The differences in location of pass- and stop-bands found by means of alternative models are highlighted and explained. The equivalence of detection of boundaries between pass- and stop-bands from the Floquet theory and from the eigenfrequency analysis of a unit symmetric periodicity cell with two sets of boundary conditions is demonstrated.